Analisis Minat Beli Produk Skintific Ditinjau dari Aspek Iklan Televisi, Celebrity Endorser dan Media Sosial (Studi Kasus Generasi Z di Kabupaten Bireuen) - Kamaruddin Kamaruddin; Fitria Fitria; Musnawar Musnawar; Nazla Asyifa (Singkite Journal, 2025)
Skintific products, with their positive image as a high-quality skincare brand, are booming in local and global markets, attracting the attention of Generation Z, particularly students. The numerous media outlets promoting them, whether through influencers or brand ambassadors on social media, can strengthen the brand's image. This research will further explore the strategies that drive purchasing interest in this product. Several factors will be examined, including television advertising, celebrity endorsers, and social media. The study was conducted among Generation Z in Bireuen Regency, focusing on Skintific products. A quantitative approach was employed through a survey with questionnaires distributed to 100 respondents. The results of the study indicate that (1) television advertising, celebrity endorsers, and social media partially influence Generation Z's purchasing interest, with celebrity endorsers having the highest influence. (20) Simultaneously, all three variables significantly influence purchasing interest, contributing 76.1%.